Pengaruh Permainan Kartu Angka Terhadap Kemampuan Mengenal Lambang Bilangan Anak KB Terpadu Al-Irsyad - Suci Ramadani Manangka; Reva Khoiriyah; Nurhikmah B. Sausambu; Cilan Trianti Laadji; Marselanda Hasan; Mita Sari (Educational Journal, 2026)
This study aims to determine the effect of number card games on the ability to recognize number symbols in early childhood at Al-Irsyad Integrated Kindergarten in the 2025/2026 Academic Year. The study used a quantitative approach with a Pre-Experimental One Group Pretest-Posttest Design. The research sample consisted of 8 children in group A consisting of 6 boys and 2 girls, with a total sampling technique. Data were collected through structured observations using observation sheets for the ability to recognize number symbols which included aspects of naming, showing, matching, ordering, and imitating number shapes. Data analysis was carried out using descriptive statistics and the Wilcoxon Signed Rank Test. The results showed that the average ability to recognize number symbols in children increased from 50.40 in the pretest to 78.25 in the posttest. The Wilcoxon test results obtained a significance value of 0.012 (p <0.05), so H₀ was rejected and Hₐ was accepted. These findings indicate that number card games have a significant effect on improving the ability to recognize number symbols in early childhood. Number card games have been proven to be able to increase children's engagement, motivation to learn, and understanding of number symbols through concrete and fun learning while playing activities. Therefore, number card games can be used as an effective alternative learning medium in developing early childhood numeracy skills.